Carbidopa/levodopa dose elevation and safety concerns in Parkinson's patients: a cross-sectional and cohort design - Michael S Okun; Peter Schmidt; David W Brodell; Nicole T Stanford; Charles E Jacobson (BMJ Open)
Objective Sinemet, a combination drug containing carbidopa and levodopa is considered the gold standard therapy for the treatment of Parkinson's disease (PD). When approved by the Food and Drug Administration (FDA) in 1988, a maximum daily dosage limit of 800 mg (eight tablets) of the 25/100 carbidopa/levodopa formulation was introduced. Overall, the FDA approval was a historic success; however, the pill limit has been hardcoded into many online medical record systems. This study investigates the 800 mg threshold by using a prospectively collected database of patient information.Design A retrospective cohort study: (Part I) cross-sectional, (Part II) longitudinal.Setting and participants PD patients at a Movement Disorders Center in a large academic, tertiary medical setting.Outcome measures An analysis was performed using carbidopa/levodopa at dosages below and above the 800 mg threshold. A secondary analysis was then performed using two consecutive clinic visits to determine the effects of crossing the 800 mg threshold. Comparisons were made on standardised scales.Results There was no significant difference in motor, mood and quality-of-life scores in patients consuming below and above the 800 mg carbidopa/levodopa threshold, though a mild worsening in dyskinesia duration was noted without worsening in dyskinesia pain and disability. In PD patients who crossed the 800 mg threshold between two consecutive clinic visits, a significant improvement in depressive symptoms and quality-of-life measures was demonstrated, and in these patients there was no worsening of motor fluctuations or dyskinesia.Conclusions The data suggest that PD patients have the potential for enhanced clinical benefits when eclipsing the 800 mg carbidopa/levodopa threshold. Many patients will likely need to eclipse the 800 mg threshold and pharmacies and insurance companies should be aware of the requirements that may extend beyond approval limits.